The crystallinity and thermal degradation behaviour of polyamide 6/Oil Based Mud Fillers (PA6/OBMFs) nanocomposites. (January 2019) - Siddique, Shohel; Kwoffie, Lorraine; Addae-Afoakwa, Kofi; Yates, Kyari; Njuguna, James
Abstract: The crystallinity and thermal degradation behaviours of Polyamide 6/Oil Based Mud Fillers (PA6/OBMFs) nanocomposites have been investigated using differential scanning and thermogravimetry (TGA). The TGA indicates the onset decomposition temperature of D1/2 (half-decomposition) is 16 °C higher for PA6 with 10.0 wt% of OBMFs than that of PA6, whereas the lowest onset decomposition temperature difference among the nanocomposites and neat PA6 is 8 °C for PA6 with 7.5 wt% of OBMFs. However PA6 with 5.0 wt % OBMFs nanocomposite has taken the longest time (1 min 36 s more than neat PA6) to reach D1/2. It can be deduced in this study that PA6 with 5.0 wt % OBMFs nanocomposite provided the maximum heat resistant property whereas PA6 with 7.5 wt % OBMFs nanocomposite showed the maximum heat absorbance property among different nanocomposites and PA6 with 10.0 wt % exhibited the maximum thermal stability. There is a sigmoidal curve generated based on the TIF and wt% filler content value which shows three significant points at intersections of 50% TIF line which are highlighted as exfoliation (4.2 wt%), intercalation (6.8 wt%) and agglomeration (9.0 wt%) points. These TIF values explained the investigated heat resistant, heat capacity and thermal stability properties of PA6/OBMFs nanocomposites illustrating the ratio of TIF and MAF is the key measure which can be considered as an effective approach to identify the nanomorphology of PA6/OBMFs nanocomposites. Highlights: Reclaimed clay from oil based drilling fluid waste. Demonstrates material tailorability for maximum heat resistant property, heat capacity and thermal stability. Effect of OBMFs filler contents on dispersion behaviour. Improvement in onset thermal degradation temperature. Dispersion behaviour identification based on relation between TIF and MAF.